Problem Based Learning Berbantuan Wordwall untuk Meningkatkan Kemampuan Pemecahan Masalah Matematis pada Siswa Kelas III SD - Fernando, Yogi; Irawati, Riana; Sunaengsih, Cucun (Indo-MathEdu Intellectuals Journal, 2024)
This study aims to determine the improvement of students' mathematical problem-solving skills by applying wordwall-assisted problem-based learning to mathematics learning of diagrams, figures, and bars in grade III elementary school students. The approach taken in this study is quantitative with a quasi-experimental method with a nonequivalent control group design. The data collection technique uses a question test. Quantitative data analysis techniques with hypothesis tests. The results of this study are that there is an increase in students' mathematical problem-solving skills between pretest and posttest in the experimental class. There was a difference in the average result of the pretest of 21.41 and the average result of the posttest of 53.94. Then, an average difference test was carried out using the wilcoxon test with the acquisition of Asymp.Sig values. (2-tailed) of 0.000 < 0.05 hypotheses were accepted. There was a difference in the improvement of students' mathematical problem-solving skills between the results of pretet and posttest in the experimental class. The calculation of the N-gain test in the experimental class was 0.43 with medium interpretation and the control class was 0.08 with low interpretation. Based on the results of this study, it can be concluded that the use of problem-based learning assisted by wordwalls can improve students' mathematical problem-solving skills